Today’s university as an organization: In the background of the institution - Pérez Morales, Flor de Liz (Emerging Trends in Education, 2022)
The figure of Luis Montaño Hirose is drawn in his academic history. His name is associated with the Universidad Autónoma Metropolitana (UAM), Unidad Iztapalapa, where he has been a full-time professor since 1981. His reflections become substantive when it comes to understanding the world, a sharp look that points to many issues, but particularly those that disrupt universities, organizations, and the complexities that nestle in the social spaces of human experiences Translated with www.DeepL.com/Translator (free version)